Reading Comprehension Interventions for Students With Autism Spectrum Disorders: An Alternating Treatments Comparison - Solis, Michael; El Zein, Farah; Vaughn, Sharon; McCulley, Lisa V.; Falcomata, Terry S. (Focus on autism and other developmental disabilities, 2016)
We conducted two separate but related single-case studies using alternating treatment designs to investigate the effects of two single-component reading interventions: question development and anaphoric cueing. In each study, we compared a typical intervention approach (Study 1, question development; Study 2, anaphoric cueing) with an alternate approach that included the addition of applied behavior analysis (ABA) techniques. The treatments that included ABA techniques were designed to improve the performance of students with autism spectrum disorders (ASD) on curriculum-based measures (CBM) of reading and on-task behavior measures during the reading tasks. The ABA techniques included the use of visual supports, a token economy, and the use of readings based on the perseverative interests of students. Four students in Grades 3 to 5 identified with ASD participated—two students in each study. Study 1 evaluated the relative effects of question development plus ABA compared with question development on CBM reading probes and an on-task behavior measure for two students. Study 2 evaluated the relative effects of anaphoric cueing plus ABA compared with anaphoric cueing on CBM reading probes and an on-task behavior measure for two students. The results indicated that the treatments that included ABA techniques were more effective than treatments that did not include ABA. These data support the use of ABA techniques for the enhancement of question development and anaphoric cueing as a means to improve reading comprehension and on-task behavior for students with ASD.